Issues and Challenges Faced by Farmers in Paddy Cultivation: A Case Study of Crop Reinsurance Scheme Proposed by Agrocaptive in Malaysia - Ashwiny, Chandra Segaran (2022)
Paddy is regarded as the most significant crop in Malaysia as the great majority of the population’s staple food is rice and paddy crop serves as the community’s main source of income and survival, particularly for landless agricultural labourers and small-scale farmers. Following this, the research objectives of this study were twofold: 1) identifying the issues and challenges faced by farmers in paddy cultivation and 2) examining the impact of crop reinsurance scheme to AgroCaptive. Using qualitative research design, data was collected through semi-structured interview with the two project managers in charge of Crop Insurance Scheme in AgroCaptive, Malaysia. Findings indicate that the major losses faced by farmers is flash flood and heavy rainfall which destroys their paddy land thus, crop insurance is necessary to compensate for the losses. The current coverage provided to paddy farmers are not sufficient to pay for their huge losses and farmers are only willing to pay for the crop insurance with small amount of premium. Therefore, introducing Crop Insurance Scheme to the farmers where the premium subsidized by the government will increase the output of the paddy. AgroCaptive The reinsurance scheme protects the AgroCaptive to compensate the catastrophic losses of paddy cultivation and planting costs. However, educating the marketing agencies as well as farmers about this crop insurance scheme is a crucial too. As a result, this research provided a more in-depth understanding of the crop insurance scheme, which contributed to academia, industry and Government. Recommendations were also be provided to improve the research’s limitation when carrying out future research.